Islam dan Negara: Negosiasi Dispensasi Nikah Pada Pengadilan Agama di Indonesia - Zumrotun, Siti; Widiyanto, Asfa (Lentera: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This study aims to identify the reasons and considerations of judges in granting marriage dispensation applications in the midst of changes to the marriage law regarding marriage age limits. The research method used was qualitative with a philosophical juridical approach, involving interviews, observation, and document analysis. Data were analyzed inductively, starting from data collection to the development of hypotheses that were tested iteratively using triangulation techniques. The results revealed several factors behind the marriage dispensation applications, such as the existence of sexual relations and pregnancy outside marriage, love and dating relationships, lack of parental supervision, and low economic and family education. The judge looked at the application to make sure it wouldn't have even worse effects. He used maqashid sharia and fiqhiyah rules to decide that stopping mafsadat (damage) was more important than getting maslahah (benefits). Another consideration is the obligation to marry for those who are worried about falling into adultery. The decision on marriage dispensation is a dilemma for judges because it contradicts child protection and the prohibition of underage marriage but is necessary to avoid worse consequences